Efektivitas Website Desa Malasari Dan Peran Internet Opinion Leader (Effectiveness of Malasari Village Website and Role of Internet Opinion Leader) - Siska Mulyawaty; Pudji Muljono; Kudang Boro Seminar (Institut Pertanian Bogor, 2016)
Utilization of Information and Communication Technology (ICT) is one solution to deliver information of governance and public services optimally to the village level. This research aimed to analyze website visitor characteristics, dimensions of website quality, role of internet opinion leader, and effectivenes of village website, also to analyze the correlation between three variables with effectiveness of village website. This study used correlational approach of quantitative. Data analysis used descriptive and inferential statistical analysis, also t-test analysis. Collecting data used a survey method by spreading e-questionnaire to 40 website visitors of two sample groups, active members of Facebook accounts Pewarta Desa Malasari and commenters on website. Based on the characteristics of website visitors, only indicator of monthly income and frequency of accessing website correlated significantly with effectiveness of village website. Information quality has strongest correlation with the effectiveness of village website, especially on the cognitive effects. The role of internet opinion leaders has no significant correlation with effectiveness of village website. Other findings showed that Facebook account of Pewarta Desa Malasari and Aji Panjalu acted as active internet opinion leaders. Village website can be effective as development information dissemination media by fullfil dimensions of website quality, and maximize the role of internet opinion leaders via social media. The use of social media has become important in supporting the existence of the village website, so it can do further research to see the relationship with the effectiveness of communication.Key words: effectivenness, village website, Facebook, internet opinion leader